Predasi Kumbang Penyelam Dewasa Cybister sp. (Coleoptera: Dytiscidae) terhadap Larva Nyamuk Aedes aegypti - Fiktor Imanuel Boleu; Boyke Raymond Toisuta (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The use of biocontrol agents in controlling Aedes aegypti mosquitoes can be an alternative to avoid the adverse effects of dependence on chemical insecticides. Exploration of potential local insects as biocontrol agents is important in maintaining the balance of the ecosystem. This study aims to determine the predation rate of the adult diving beetle Cybister sp. against Ae. mosquito larvae. aegypti. This experimental research was carried out at the Integrated MIPA Laboratory, Halmahera University. A total of 1 predator and 30 late instar larvae of Ae. aegypti was placed in an aquarium (20 cm x 14 cm x 14 cm, 2 L capacity) containing 1 liter of water. Observation of predation of Cybister sp. adults against Ae. aegypti was carried out for 72 hours at intervals of 6 hours. This predation experiment was carried out with three replicates. Analysis of the predation rate of Ae. aegypti refers to a mathematical model. The statistical test used was correlation to see the speed of larval predation and analysis of variance. The results showed that the adult diving beetle Cybister sp. able to reduce the number of Ae. aegypti with a predation rate in 12 hour intervals of 0.755; 0.294; 0.188; and 0.132 per hour respectively. This predation showed an accurate and significant relationship (R2 = 0.8608; P <0.05). The conclusions of this study indicate that the adult diving beetle Cybister sp. able to reduce the number of Ae. aegypti with a predation rate in 12 hour intervals of 0.755; 0.294; 0.188; and 0.132 per hour respectively, and statistically the predation shows an accurate and significant relationship.